Jogo de astronomia utilizando a realidade aumentada - Costa, Edelson Moreira da (2017)
In this work, we have developed a board game, using augmented reality, to be used in the teaching of solar system in astronomy. Augmented reality makes possible to insert objects into a virtual image at real time. In the elaboration of this game, we have used the software 3Ds max for the creation and animation of the planets and the sun, and a program called ARToolKit that allowed to associate the planets and the spaceship, which was also created in 3Ds Max, to the board in real time. This educational product (the board game) was applied to students in the first year of the high school, of the Federal Institute of Alagoas (IFAL) Campus Satuba. The results showed that all of them liked the game. The students said that the game facilitated the understanding of the subject (about the solar system) and making the class more dynamic. In addition, we applied a questionnaire before and after the application of the game, and it was obtained that in the ending of the game they got all the answers in the questionnaire right, which had not happened in the first time that they answered the questionnaire (before the game), which indicated that the game played a central role inassimilating what was studied. They also felt that using this game provided them the opportunity to interact and perform teamwork, which was also a great result. We hope that this board game can be used by teachers (especially by physics teachers) as an aid in their pedagogical practice.